Object-oriented Iterative-recursive Algorithm for Thermal-hydraulic Systems Simulation - Govorushchenko, Yuriy Nikolaevich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
The description of the object-oriented iterative-recursive algorithm for thermal-hydraulic systems simulation is presented, which intended for wide range of practical problems and characterized by effectiveness, flexibility, extensibility and portability.  Some examples of advantages of the object-oriented approach (encapsulation, inheritance, composition etc.) to the analysis of thermodynamic cycles are demonstrated, in particular, the possibility of the turbomachine’s detailed flow path aerodynamic calculation in common with the cycle’s simulation is justified. The features of the software implementation using a general purpose algorithmic language are described and the expediency of integration of the algorithm with a graphical environment for the thermal-hydraulic systems analysis is shown.